Unexpected diversity in northern Europe: trematodes from salmonid fishes in Iceland with two new species of Crepidostomum Braun, 1900 - Faltýnková, A; Pantoja, C; Skírnisson, K; Kudlai, O (Parasitology research, 2020)
In 2018 and 2019, salmonid fishes, Salmo trutta L. and Salvelinus alpinus (L.) from lakes in Iceland were assessed for trematodes during a parasitological examination. Combined morphological and molecular analyses revealed the presence of four trematode species, two of which were previously known to parasitise salmonids in Iceland, Crepidostomum farionis (Müller, 1780) and Phyllodistomum umblae (Fabricius, 1780), and the two remaining species were recognised as new to science. Morphologically and genetically, Crepidostomum brinkmanni n. sp. and C. pseudofarionis n. sp. are closely related to two European species, namely C. metoecus and C. farionis. However, C. brinkmanni n. sp. is distinct by the position of maximum body width and arrangement of vitelline follicles; C. pseudofarionis n. sp. is distinct by its stout body, position of maximum body width, size of muscular papillae relative to oral sucker and the anterior extent of vitelline follicles. The new species were previously molecularly detected in their intermediate and definitive hosts in Norway and Ukraine, but their sequences were not supplemented with any morphological characterisation. In the present study, we provide detailed morphological descriptions and molecular sequences (28S rDNA and ITS2) of the four species of trematodes detected in Iceland. The discovery of the two new species of Crepidostomum indicates that the trematode diversity in fishes in the north is higher than previously known; our finding doubles the species spectrum of fish trematodes for Iceland. The record of C. brinkmanni from Ukraine indicates that its distribution might not be limited to northern latitudes.
Keywords: Biodiversity; druhová specificita; Gorgoderidae; Island; Fish Diseases; Allocreadiidae; Iceland; fylogeneze; Lakes; Sub-Arctic; Phylogeny; ribozomální DNA; biodiverzita; infekce červy třídy Trematoda; Species Specificity; jezera; Morphology; Animals; zvířata; nemoci ryb; Trematoda; Nuclear DNA; Trematode Infections; DNA, Ribosomal; Salmonidae